Case Report: Spontaneous Resolution of an Established Iatrogenic Vertebral Arteriovenous Fistula. (February 2013) - Adams, Ashok; Allouni, Kader; Basheer, Sheikh; Evanson, Jane; Mankad, Kshitij
Vertebral artery injuries can complicate attempted cannulation of the internal jugular vein including arteriovenous fistula formation. Such a fistula may occlude spontaneously in the acute phase but once established, spontaneous occlusion is extremely unusual. To the best of our knowledge, this has not been reported in the medical literature. We present a case of a patient who developed a right-sided vertebral arteriovenous fistula following instrumentation of the neck vessels but formal angiography/intervention was declined. The reason to report this case is that follow-up magnetic resonance angiography was performed, with spontaneous resolution of the right-sided vertebral arteriovenous fistula occurring postoperatively between days 30 and 135. Endovascular treatment options are available but for those who decline intervention, this report highlights the fact that spontaneous resolution of vertebral arteriovenous fistulae can occur.